Career Development of Low-Income High School Alumni: An Interpretative Phenomenological Analysis - Tosoc, Michael (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined how low-income high school alumni described and interpreted their lived experiences in making career decisions during high school and how these experiences contributed to their career development. Anchored on Social Cognitive Career Theory, the Psychology of Working Theory, and Gottfredson’s Theory of Circumscription and Compromise, the study employed a qualitative research design using Interpretative Phenomenological Analysis (IPA). Participants were purposively selected alumni who experienced low-income conditions during their secondary education. Data were collected through semi-structured interviews and analyzed using IPA procedures, including close reading, initial noting, emergent theme development, and thematic interpretation. The findings revealed that career decision-making among low-income alumni was shaped by socioeconomic constraints, family responsibilities, emotional uncertainty, and personal aspirations. Participants interpreted career choices through affordability, practicality, and family obligations, often adjusting aspirations to align with available resources and perceived opportunities. Despite these challenges, their experiences contributed to the development of practical career awareness, resilience, adaptability, values clarification, self-understanding, and agency within socioeconomic limitations. Retrospective reflections further showed that participants reframed hardship as a source of motivation and recognized the importance of career guidance, mentorship, counseling, scholarship information, and family support in career planning and development. The study concluded that career development among low-income students is influenced by both structural constraints and individual meaning-making processes. It highlights the need for context-sensitive, family-inclusive, and economically responsive career development programs that provide practical information, emotional support, and access to educational opportunities. The findings support Sustainable Development Goal (SDG) 4 (Quality Education) and SDG 10 (Reduced Inequalities) by emphasizing equitable access to career guidance and educational support for economically disadvantaged learners. The study contributes to educational and social sustainability by informing inclusive career development initiatives that promote informed decision-making, career readiness, and long-term social mobility.
Keywords: Career Decision-Making; Career Development; Interpretative Phenomenological Analysis; Lived Experiences; Low-Income Alumni; Meaning-Making; Resilience; Socioeconomic Constraints; Student Support Services